An environmental flow to an ephemeral creek increases the input of carbon and nutrients to a downstream receiving river - Liu, Xiaoying; Watts, Robyn J.; Dyer, James (Frontiers in Environmental Science, 2024)
Although intermittent and ephemeral rivers lack surface flow for part of the year, they provide vital refuges for biota in otherwise dry semi-arid and arid landscapes. The hydrology of many such rivers has been altered due to river regulation and climate change. Environmental flows can be delivered to address the negative impacts of regulated flows, however there is limited knowledge of how dry ephemeral ecosystems respond following environmental flows. This study examined changes in water quality of the ephemeral Thule Creek in the southern Murray-Darling Basin, Australia, following delivery of environmental water from an irrigation canal. We also examined how the environmental flow influenced water quality of Wakool River that receives inflows from Thule Creek. Six sites in Thule Creek, three in Wakool River, and one in Yarraman irrigation channel (source water) were monitored for dissolved organic carbon (DOC), nutrients and dissolved oxygen (DO) once per week over 15 weeks from October 2019 to January 2020. The environmental flow resulted in high DOC concentrations (4.4-76 mg/L) and low DO levels (0.4-11.2 mg/L) at sites in Thule Creek that were on some dates below the threshold for fish stress (< 4 mg/L), there were no fish kills observed during the environmental flow. Carbon-rich and nutrient-rich pulses (DOC > 10 mg/L, total phosphorus 94 µg/L, total nitrogen 1125 µg/L) were detected in the Wakool River downstream of Thule Creek confluence compared to the Wakool River upstream of Thule Creek confluence (DOC 6.6 mg/L, total phosphorus 64 µg/L, total nitrogen 805 µg/L) following the environmental flow in Thule Creek connected with Wakool River. This research provides an example of how irrigation canal networks can be used to deliver environmental water to an ephemeral river to maintain refuges and contribute to the productivity of a receiving river further downstream. Careful management of the timing, volume and duration of environmental flows in arid or semi-arid landscapes is needed to avoid the development of poor water quality during, or following, the delivery of environmental water.